Protestants abroad : how missionaries tried to change the world but changed America - Hollinger, David A. (2017)
Between the 1890s and the Vietnam era, many thousands of American Protestant missionaries were sent to live throughout the non-European world. They expected to change the people they encountered, but those foreign people ended up transforming the missionaries. Their experience abroad made many of these missionaries and their children critical of racism, imperialism, and religious orthodoxy. When they returned home, they brought new liberal values back to their own society. Protestants Abroad reveals the untold story of how these missionary-connected individuals left an enduring mark on American public life as writers, diplomats, academics, church officials, publishers, foundation executives, and social activists. --
Includes bibliographical references and index
Keywords: Missions, American -- History; Protestant churches -- Missions -- History; HISTORY / United States / General; HISTORY / World; HISTORY / Social History; United States; History